Two-enzyme cascade catalyzed trideuteromethylative modification of natural products. (17th December 2022) - Zou, Zi-Ruo; Zhang, Kai; Han, Ting-Yan; Zhou, Qiang; Lin, Shuangjun; Hou, Xian-Feng; Tang, Gong-Li
Abstract: Site-selective incorporation of the trideuterated "magic methyl" group may provide profound pharmacological benefits, which has been considered as an important tool for drug optimization and development in medicinal chemistry. S-adenosyl-L-methionine (SAM) usually acts as the methyl donor under the catalysis of SAM-dependent methyltransferases (MTs), which transfer a methyl group from SAM to substrates, and are widely reported for methylation in natural product biosynthesis. However, it is difficult to introduce other high-value functional groups to substrates in this way since SAM analogs are not easy to obtain in biological methods. Herein we report that trideuterated SAM can be obtained from S-adenosylhomocysterine (SAH) and trideuterated methyl iodide (CD3 I) under the participation of halide methyltransferase (HMT). Subsequent one-pot cascades with different MTs achieved the regioselective trideuteromethylation of three natural products, which indicated that trideuterated SAM can be accepted as a co-substrate by C-, N-, O-specific MTs for enzyme-catalyzed trideuteromethylation of natural products.